Considerations on Political Ethics in (Environmental) History: Scales and the Presentism of Devastation - Arruda, Gilmar [UNESP]; Colacios, Roger (Historia Ambiental Latinoamericana y Caribena - HALAC, 2019)
This article has as theme the possibility of the discussion about the ethical-political principles in the Environmental History. The considerations made here has as a basis the perspective of present crisis and environmental devastation. Both are understanded as a violation of the non-human rights, perpetrate by a decadal war against the natural world, drive by the capitalism and his economical, political and social agendas inside this temporality. The example of this theme is in the occupation process on the north of Paraná land in the 20 century and keeping until today, it nor only transformed the forestall landscape in the region, but decimate millions of trees and animals' species and maybe billions of microorganisms. Is waited with this discussion to promote a debate about the analytical ways of the Environmental History e about the responsibilities of the researchers, among many others, as a knowledge promoter of the relationships between human beings and non-humans.
Keywords: Crime; Environmental history; Ethical-political turn; Present time